QUIMIOTERAPIA DE BANANA ‘PRATA ANÃ’ NO CONTROLE DE PODRIDÕES EM PÓS-COLHEITA - Moraes, W.s.; Zambolim, L.; Lima, J.d. [UNESP] (Instituto Biológico, 2021)
CHEMOTHERAPY OF “PRATA ANÃ” BANANAS FOR POST-HARVEST ROT CONTROL. Anthracnose (Colletotrichum musae) and crown rots (fungi complex) are the main diseases that occur in the banana crop post-harvest. This poses the challenge of prolonging the post-harvest life, increasing the disease-free period and maintaining the fruit’s food quality. The objective of this work was to evaluate the efficiency of systemic and protective fungicides in the control of postharvest rot in fruits of the banana cultivar “Prata anã” from Jaíba, Minas Gerais, Brazil. Systemic fungicides from the benzimidazole, triazole, imidazole and pyridinamine chemical groups were evaluated in the dosages 0, 125, 250 and 500 mL.L-1 or mg.L-1, after immersion for 3 minutes, in environmental conditions (18-23º C and 60–85% RU). Procloraz (125 mL.L-1) and propiconazole (250 mL.L-1) were the most efficient for preventing the incidence of rot in bananas inoculated with C. musae. Higher dosages caused toxicity in the fruits. The benzimidazois were not efficient in the control of rot, even at the highest dosage used (500 mL.L-1), showing results similar to standard fungicide (benomil) and the control treatment without fungicide. The fungicide propiconazole at the dosage 250 mL.L-1proved to be effective for use in the post-harvest bananas, not causing toxicity in the “Prata anã” banana fruits.

A antracnose (Colletotrichum musae) e a podridão da coroa (complexo de fungos) são as principais doenças que ocorrem em pós-colheita de bananas. Prolongar a vida pós-colheita, aumentar o período livre dessas doenças e manter a qualidade comestível dos frutos passam a ser o grande desafio. O objetivo do trabalho foi avaliar a eficiência de fungicidas sistêmicos e protetores no controle de podridões em frutos de banana ‘Prata anã’ proveniente de Jaíba, Minas Gerais. Fungicidas sistêmicos dos grupos químicos dos benzimidazóis, triazóis, imidazóis e piridinamina protetor foram avaliados nas dosagens de 0, 125, 250 e 500 mL.L-1 ou mg.L-1, após imersão por 3 minutos, sob condições ambientes (18-23°C e 60-85 % UR). Procloraz (125 mL.L-1) e propiconazole (250 mL.L-1) foram os mais eficientes em evitar a incidência de podridões em bananas inoculadas com C. musae. Dosagens superiores a estas causaram toxidez aos frutos. Os benzimidazóis não foram eficientes no controle das podridões, mesmo na maior dosagem utilizada (500 mL.L-1), mostrando-se semelhantes ao fungicida padrão (benomil) e ao controle não-tratado. A eficiência do fungicida propiconazole foi confirmada para uso em pós-colheita da cultura da bananeira, mostrando-se efetivo na dosagem de 250 mL.L-1, sem causar toxidez em banana ‘Prata anã’.
CHEMOTHERAPY OF “PRATA ANÃ” BANANAS FOR POST-HARVEST ROT CONTROL
Keywords: Chemical control; anthracnose; crown rot; fungi; disease; fungicide; Controle químico; antracnose; fungos; podridão da coroa; doenças; fungicida